Endothelial Cell Behavior Is Determined by Receptor Clustering Induced by Thrombospondin-1 - Morandi, Verônica; Petrik, Jim; Lawler, Jack (Frontiers in Cell and Developmental Biology, 2021)
The thrombospondins (TSPs) are a family of multimeric extracellular matrix proteins that dynamically regulate cellular behavior and response to stimuli. In so doing, the TSPs directly and indirectly affect biological processes such as embryonic development, wound healing, immune response, angiogenesis and cancer progression. Many of the direct effects of TSP-1 result from the engagement of a wide range of cell surface receptors including syndecans, low density lipoprotein receptor-related protein 1 (LRP1), CD36, integrins and CD47. Different or even opposing outcomes of TSP-1 actions in certain pathologic contexts may occur, depending on the structural/functional domain involved. To expedite response to external stimuli, these receptors, along with vascular endothelial growth factor receptor 2 (VEGFR2) and Src family kinases, are present in specific membrane microdomains, such as lipid rafts or tetraspanin-enriched microdomains. The molecular organization of these membrane microdomains and their constituents is modulated by TSP-1. In this review, we will describe how the presence of TSP-1 at the plasma membrane affects endothelial cell signal transduction and angiogenesis.